Comparative analysis of joint commission international and healthcare information and management systems - electronic medical record adoption model measurement models using text mining - Cece, Sinem; Köse, İlker (Association of Nurse Managers, 2022)
Introduction: Health service quality refers to all efforts to prevent a negative outcome in the health status of individuals. For this reason, measuring and evaluating the quality of health services is important to increase the quality of services provided. Aim: In this study, Joint Commission International’s (JCI) accepted indicator-based health service quality measurement model and the Healthcare Information and Management Systems Society’s (HIMSS)-Electronic Medical Record Adoption Model (EMRAM) are discussed. Method: This research used the bag-of-words model (BoW), a text mining method. Result: As a result of the analysis, the similarity of keywords (as unigrams) used in all of the guides was found to be approximately 33%, the bigram similarity was 6% and the trigram similarity was 3%. Conclusion: The fact that the similarity between the two models is not higher can be explained by the fact that, unlike JCI, the HIMSS EMRAM model handles the quality of health services with a digitalization axis. Text mining opens up new research areas as a method for comparing quality standards with new and interesting results.

Giriş: Sağlık hizmet kalitesi, bireylerin sağlık durumlarında olumsuz bir sonucun oluşmasını önlemeye yönelik tüm çabaları belirtmektedir. Bu nedenle sağlık hizmetlerinin kalitesinin ölçülmesi ve değerlendirilmesi verilen hizmetin kalitesinin artırılması açısından önemlidir. Amaç: Bu çalışmada, gösterge tabanlı sağlık hizmeti kalitesi ölçüm modeli Uluslararası Ortak Komisyon (Joint Commission International-JCI) ve Sağlık Bilgi Yönetim Sistemleri Topluluğu (Healthcare Information and Management Systems Society-HIMSS)- Elektronik Sağlık Kaydı Benimseme Modeli (Electronic Medical Record Adoption Model-EMRAM) ele alınmaktadır. Yöntem: Bu araştırmada, bir metin madenciliği yöntemi olan sözcük torbası modeli (bag-of-words/BoW) kullanılmıştır. Bulgular: Analiz sonucunda tüm rehberlerde kullanılan anahtar sözcüklerin tek harfli sözcük (unigram) benzerliği yaklaşık %33, iki harfli sözcük (bigram) benzerliği %6 ve üç harfli sözcük (trigram) benzerliği %3 olarak bulunmuştur. Sonuç: İki model arasındaki benzerliğin fazla olmaması, JCI’dan farklı olarak HIMSS- EMRAM modelinin sağlık hizmet kalitesini dijitalleşme ekseniyle ele almasıyla açıklanabilir. Çalışmada metin madenciliği yönteminin kullanılması, kalite standartlarının yeni ve ilginç sonuçlarla karşılaştırma olanağı sağlamaktadır.
Uluslararası Ortak Komisyon (JCI) ve Sağlık Bilgi Yönetim Sistemleri Topluluğu (HIMSS) - Elektronik Sağlık Kaydı Benimseme Modelinin (EMRAM) metin madenciliği yöntemi ile karşılaştırmalı analizi
Keywords: Quality of Healthcare; Quality Indicators Healthcare; Medical Informatics; Data Analysis; Text Mining; Sağlıkta Kalite; Sağlıkta Kalite Göstergeleri; Tıp Bilişimi; Veri Analizi; Metin Madenciliği